Fine Motor Stimulation for Pre-Writing Skills through Geometric Pattern Cutting Activities in Early Childhood - Rina Nur Sholichah; Ezif Rizqi Imtihana (Manunggal Halim Jaya, 2026)
This study aims to describe fine motor stimulation strategies in improving children's pre-writing skills through cutting activities at KB Pelangi. This research employed a qualitative descriptive approach involving 17 children as research subjects. Data were collected through observation, interviews, and documentation, while data analysis used the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The results indicate that cutting activities conducted in a gradual manner, supported by engaging learning media and intensive teacher guidance, can effectively enhance children's fine motor skills. This improvement is reflected in children's ability to hold scissors properly, better hand-eye coordination, ability to follow simple line patterns, and increased readiness for pre-writing activities. Therefore, cutting activities are effective as a strategy for stimulating fine motor development in early childhood.